Capacidade nematicida de Bacillus spp. sobre larvas de Haemonchus contortus - Sinott, Marina Cunha (2012)
Parasitic infections are the major cause of losses in livestock, particularly those involving sheep. Multidrug resistance makes the problem even more worrying because in addition to pathogens, parasites do not appear more susceptible to the active principles. Currently, for the progress to occur in sheep farming, there must be a need to seek alternatives that reduce the dependence on the success of the activity to the emergence of a molecule that makes a lack reduced, selective toxicity, and high degree of effectiveness in combating infestation. This context has led to studies in order to investigate the behavior of strains Bacillusspp, when in contact with eggs and young larvae of the forms tricostrongilídeo Haemonchuscontortus, which is undoubtedly the most pathogenic for sheep that are raised in the field. It was verified through in vitro tests, which B. circulans showed an 80.9% reduction in the number of larvae when compared to control groups. This reduction was also observed in the tests made in vivo, as well as the residual capacity of the agent through tests performed with Bacillus transformed and expressing the GFP gene.